MODERASI MOTIVASI BERPRESTASI PADA PENGARUH TINGKAT KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR - Y Mulyani; Sumartini Sumartini; S Kurniawati (Pendidikan Ekonomi FPEB Universitas Pendidikan Indonesia, 2022)
This research is motivated by the fact that there are still many students whose learning outcomes have not reached the Minimum Completeness Criteria (KKM) in economic subjects seen from the results of the Odd Semester Final Examination (PAS) in Senior High School Negeri, South Bandung Regency in the 2021/2022 school year. This research to determine the role of Achievement Motivation in Moderating the effect of Emotional Intelligence on Learning Outcomes. The population in this study were high school students in the south Bandung Regency with a populationn of 959 students from five schools, using random sampling technique so that a sample of 283 students was obtained. The Method used in this study in an explanatory survey, with technical data analysis using the MRA test or Moderated Regression Analysis with moderated variables. The results of this study indicate that (i) The General description of Emotional Intelligence and Achievement Motivation has a moderate category (ii) Emotional Intelligence middle affects learning Outcomes, (iii) Achievement Motivation can negatively moderate or weaken the influence of Emotional Intelligence on Learning Outcomes.